Experimental investigations on ethylene-air Continuous Rotating Detonation wave in the hollow chamber with Laval nozzle. (October 2018) - Peng, Haoyang; Liu, Weidong; Liu, Shijie; Zhang, Hailong
Abstract: The ethylene-air Continuous Rotating Detonation (CRD) has been experimentally achieved with large operating domain, little velocity deficit and notable pressure rise in the hollow chamber with Laval nozzle. The results show that the lean limit increases while operating domain decreases with contraction ratio increasing. Deflagration flame in recirculation zone and larger width combustor enable the ethylene-air CRD to be readily achieved. Three different propagation modes are presented. Most of the achieved CRD experiments are single-wave mode. The highest frequency and velocity are 6.10 kHz and 1915.40 m/s respectively. Two-waves mode can be obtained when contraction ratio is 12. Sawtooth wave mode appears around lean limit when contraction ratio is 1, 2 and 4. Sawtooth wave, as a critical condition, can be transformed into typical CRD wave or extinguish. For contraction ratios of 1, 2, 4 and 6, the propagation stability increases with equivalence ratio (ER) increasing. For contraction ratios of 8, 10 and 12, the stability decreases with a concomitant increase of ER. The contraction ratios of 2 and 4 are beneficial for CRD wave to propagate with high frequency and stability. The study will deepen the understanding of ethylene-air CRD and enrich the combustor design theory of CRD Engine fueled by hydrocarbon fuels. Highlights: The ethylene-air Continuous Rotating Detonation is experimentally achieved. The hollow chamber contributes to Continuous Rotating Detonation realization. The highest frequency and velocity are 6.10 kHz and 1915.40 m/s, respectively. The Laval nozzles ( ε =2, 4) are beneficial for detonation wave propagating.